What asylum and refugee policies do Europeans want? Evidence from a cross-national conjoint experiment - Anne-Marie Jeannet; Tobias Heidland; Martin Ruhs (European Union Politics, 2021)
The protection of asylum seekers and refugees has become one of the most politically divisive issues in the European Union, yet there has been a lack of research on public preferences for asylum and refugee policies. This article analyzes which policies Europeans prefer and why. We advance a theoretical framework that explains how asylum and refugee policies that use limits and conditions enable individuals to resolve conflicting humanitarian and perceived national interest logics. Using an original conjoint experiment in eight countries, we demonstrate that Europeans prefer policies that provide refugee protection but also impose control through limits or conditions. In contrast to the divisive political debates between European Union member states, we find consistent public preferences across European countries.
Keywords: 330; asylum and refugee policy; Europe; migration; policy preferences